2017
DOI: 10.1515/hacq-2017-0001
|View full text |Cite
|
Sign up to set email alerts
|

First confirmed record of Elodea canadensis Michx. (Hydrocharitaceae) in Greece

Abstract: The paper confirms the presence of Elodea canadensis Michx. in Greece and outlines the history of contradictory relevant reports. This is also the first report of the species' presence in the transboundary lake Great Prespa. IzvlečekV članku smo potrdili prisotnost vrste Elodea canadensis Michx. v Grčiji in predstavljamo zgodovino pomembnih, a nasprotujočih si poročil o njenem uspevanju. To je obenem tudi prva potrditev prisotnosti vrste v čezmejnem Velikem Prespanskem jezeru.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…In the Greek part of Lake Prespa, E. canadensis was found accompanying Myriophyllum spicatum , Trapa natans , Potamogeton perfoliatus , Ceratophyllum demersum , etc. [ 45 ]. Such a list of accompanying species is in line with the high frequency of E. canadensis within the stands belonging to the vegetation of the class Potamogetonetea , as documented in Czechia [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the Greek part of Lake Prespa, E. canadensis was found accompanying Myriophyllum spicatum , Trapa natans , Potamogeton perfoliatus , Ceratophyllum demersum , etc. [ 45 ]. Such a list of accompanying species is in line with the high frequency of E. canadensis within the stands belonging to the vegetation of the class Potamogetonetea , as documented in Czechia [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to Lansdown et al (2016), it is naturalized in 10 South-Eastern European country including European Turkey. Elodea canadensis was rst collected in Greece in 2014 from the Lake Great Prespa (Poulis and Zervas 2017). It is also naturalized in different parts of Bulgaria including the Turkish border.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is found in 10 South Eastern European countries (Lansdown et al 2016). Elodea canadensis herbarium specimens were rst collected from Greece in 2014 from the Lake Great Prespa located at the northwestern corner of the country (Poulis and Zervas 2017). Assyov and Petrova (2012) showed that in addition to other parts of Bulgaria, E. canadensis has a distribution along the Turkish border.…”
Section: Introductionmentioning
confidence: 99%
“…According toLansdown et al (2016), it is naturalized in 10 South-Eastern European country including European Turkey. Elodea canadensis was rst collected in Greece in 2014 from the Lake Great Prespa(Poulis and Zervas 2017). It is also naturalized in different parts of Bulgaria including the Turkish border.…”
mentioning
confidence: 99%